Inequality trends in Romania - Precupețu, Iuliana (Calitatea Vieții, 2013)
Romania illustrates a case of remarkable growth of income inequality during the transformation period. The country is one of the most unequal in the EU, in regard to income inequality, while a range of various inequalities characterize its social setup. This paper is a descriptive attempt of highlighting three dimensions of inequality in Romania: income, labour market and education inequality. First, the article concentrates on income inequality with the aim of understanding the pattern of growing inequalities, in time. Secondly, the paper focuses on poverty and poverty profiles, by employing two measures of poverty, relative and absolute, with the aims of understanding the trends in the evolution of poverty and of highlighting the most exposed groups to poverty. Labour market inequality is treated in the next section, and the final section is dedicated to educational inequality. The paper uses NIS national data, as well as Eurostat data. The data show that even though Romania has the lowest median equivalised income in the EU, it also displays a high level of income inequality. Inequalities are structured by socio-demographic groups, as well as at territorial level, by region, residence and type of community. Moreover, there is no evidence that the existing divides tend to lower, on the contrary, they already seem deeply-rooted, and tend to maintain.